2023
DOI: 10.1111/pere.12505
|View full text |Cite
|
Sign up to set email alerts
|

Understanding relationship satisfaction during COVID‐19: Assessing unstable work experiences and negative communication

Abstract: The coronavirus (COVID‐19) pandemic resulted in economic concerns and disruptions in daily life for many families, which may amplify relational strains and create new tensions between romantic partners. Economic stressors may be particularly salient to later relationship quality in the context of more negative relationship functioning. This study investigated dyadic trajectories of relationship satisfaction in 116 different‐sex couples over a 6‐month period during the pandemic. We explored the impact of unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…In a nationally representative sample of about 1,700 different-sex newlywed couples, LeBaron-Black et al (2023, 2024) employed three items from the CSI-4 and identified invariance between husbands and wives. Similarly, the measure showed invariance between men and women in a sample of 116 different-gender partners during the pandemic (Kanter et al, 2023). Finally, Lamela et al (2020) identified invariance in the CSI-4 for women in Portugal exhibiting low and high levels of depressive symptoms.…”
Section: The Importance Of Measurementmentioning
confidence: 93%
“…In a nationally representative sample of about 1,700 different-sex newlywed couples, LeBaron-Black et al (2023, 2024) employed three items from the CSI-4 and identified invariance between husbands and wives. Similarly, the measure showed invariance between men and women in a sample of 116 different-gender partners during the pandemic (Kanter et al, 2023). Finally, Lamela et al (2020) identified invariance in the CSI-4 for women in Portugal exhibiting low and high levels of depressive symptoms.…”
Section: The Importance Of Measurementmentioning
confidence: 93%